Integrals for functions with values in a partially ordered vector space - Arnoud van Rooij; Willem van Zuijlen (arXiv.org, 2015)
We consider integration of functions with values in a partially ordered vector space, and two notions of extension of the space of integrable functions. Applying both extensions to the space of real valued simple functions on a measure space leads to the classical space of integrable functions.